The association between CKD-associated pruritus and quality of life in patients undergoing hemodialysis in Pakistan: A STROBE complaint cross-sectional study. Issue 36 (September 2019) - Rehman, Inayat Ur; Chan, Kok Gan; Munib, Syed; Lee, Learn Han; Khan, Tahir Mehmood
Abstract : Abstract: Chronic kidney disease (CKD)-associated pruritus is one of the most common symptoms found in patients who undergo dialysis for CKD, leading to a compromised quality of life. This study aimed to investigate the association between CKD-associated pruritus and the quality of life in patients undergoing hemodialysis in Pakistan. A cross-sectional multicenter study was carried out from July 2016 to April 2017 in 2 tertiary care hospitals in Pakistan. Patients aged 18 years and above of both genders, undergoing hemodialysis, understood the Urdu language, and were willing to participate; were included. Of 354 recruited patients with a response rate of 100%, majority (66.1%) of the patients were males. The median (intra-quartile range [IQR]) age of patients was 42.0 [34.0–50.0] years. The prevalence of pruritus was 74%. The median [IQR] score for pruritus was 10.0 (out of possible 25) [8.0–12.0]. Multivariate linear regression revealed a statistically significant association between CKD-associated pruritus with age of patients (β = 0.031; 95% confidence interval [CI] = 0.002–0.061; P = .038), duration of CKD (β = −0.013; 95% CI = −0.023 –−0.003; P = .014) and quality of life (β= −0.949; 95% CI = −1.450; −0.449). The median [IQR] score for health-related quality of life was 52.00 [43.00–58.00]. Prevalence of CKD-associated pruritus was reported to be 74% and it negatively affected the patient's quality of life. Patients with moderate to severe CKD-associated pruritus have poor quality of life. With an increase in intensity of pruritus, the QOL score decreased among the patients undergoing hemodialysis. Abstract : Supplemental Digital Content is available in the text